Bullous pemphigoid antigen localization suggests an intracellular association with hemidesmosomes - Westgate, G E; Weaver, A C; Couchman, J R (Journal of investigative dermatology, 1985)
Autoantibodies to a normal component of stratified squamous epithelia, the bullous pemphigoid antigen (BPA), are synthesized in patients with the disease bullous pemphigoid. We have used these sera to study the distribution of BPA in vivo and in vitro. At low magnification, indirect immunofluorescent staining for BPA is linear at the basement membrane zone (BMZ) of skin and many other epithelial tissues. At higher magnification however, we observed a punctate staining pattern for BPA which was regular in appearance and suggested localization of BPA to discrete structures at the BMZ. Subsequent immunoelectron microscopy using both peroxidase and colloidal gold labeling techniques with patients' sera or IgG, revealed that BPA is associated with hemidesmosomes--putative adhesion structures at the BMZ, based on their similarity in ultrastructure to desmosomes. More specifically BPA was immunolocalized to the cytoplasmic face of hemidesmosomes and was not observed extracellularly in the basement membrane. In stratifying and nonstratifying cultures of rat keratinocytes, BPA is expressed intracellularly and not in the cell-derived matrix, unlike other known basement membrane components. These cells also synthesize BPA in vitro, and immunoprecipitation from metabolically labeled cultures revealed a 220 kD polypeptide under reducing conditions. From these observations we conclude (1) that BPA is a 220 kD polypeptide component either of or associated with hemidesmosomes, and (2) that it is localized intracellularly both in vivo and in vitro. We suggest that BPA is not normally a lamina lucida component, but that it may form part of a linkage between the cytoskeleton and the basement membrane.